Legal Analysis of Current Indonesia's Marine Protected Areas Development - Adrian Nugraha (Sriwijaya Law Review, 2021)
This paper aims to conduct a legal analysis of the development of Marine Protected Areas (MPAs) in Indonesia. This article discusses the international legal framework and national legislation related to MPAs, progress and control, and problems in developing MPAs in Indonesia and its solutions. The international legal frameworks discussed include the United Nations Convention on the Law of the Sea 1982, the Convention on Biological Diversity 1992, and Code of Conduct for Responsible Fisheries 1995. Subsequently, the Indonesian legislation analyzed includes the Act on Conservation of Living Resources and their Ecosystems, the Act concerning Fisheries, the Act concerning the Management of Coastal Areas and Small Islands, and the Act on Marine Affairs. The progress and control of the establishment of MPAs in Indonesia have now reached the target area of more than twenty million hectares. Apart from the success of these achievements, Indonesia also has problems in developing MPAs. Current problems related to MPA development include dualism of permits, conflicts over zoning and regional spatial planning, multiple interpretations of penal sanctions, and overlapping management authorities between government agencies. The solutions offered to solve these problems include synchronizing marine tourism permits, integrating zoning and spatial plans into one regional government regulation, imposing the most severe criminal sanctions for perpetrators of destroying marine ecosystems, and transfer of full authority over the management of seven marine protected areas to the Ministry of Marine Affairs and Fisheries.